الألفاظ الغريبة ومعانيها فى القرآن الكريم عند ابن عباس وعلاقتها بالشعر العربيAl-Alfādz al-Gharībah wa ma’ānīha fī al-Qur’ān al-Karīm ‘inda Ibni ‘Abbās wa ‘Alāqatihā bi as-Syi’ri al-‘Arabiy - Sudomro Hasibuan (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2020)
This research is based on the assumption that strange expressions are found in the al-Qur’an al-Karim according to Ibn Abbas, and it was written by Imam al-Suyuti in his book “The Perfection in the Sciences of the Qur’an”. This study has many benefits from the apparatus of its languages and its meanings and the expansion of sciences in it. Among the apparatus of its significance, it is more important for us, as Muslims, that we can understand it to memorize its truth and deepen our understanding of this noble book. Based on the problems of this research, the researcher mentions the objectives of this research in three sections: 1) Information on strange expressions in the al-Qur’an al-Karim of Suras are mentioned. 2) Information on the meanings of strange words in the al-Qur’an al-Karim of surah mentioned. 3) The media states that it has a relationship between the strange words in the al-Qur’an al-Karim of suras mentioned with the Arabic poetry of Ibn Abbas.Keywords: Al-Alfādz al-Gharībah, al-Qur’ān al-Karīm, as-Syi’ri al-‘Arabiy, ‘Ilmi ad-Dalālah